(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
Considering the increasing attention in recent times to improving management in business entities, we conducted research and analysis of the organization level of the management system in state-owned enterprises, management principles and methods, and their positive consequences.